Analysis of the Interests of MA DDI Kalukunangka Students in Continuing Higher Education Studies - Sofyan Umar; Jusniati H (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
Education lasts a lifetime, starting from birth. In the process of development, humans need education, through this process humans develop rapidly because the environment provides assistance in human development. The educational environment can be found at home, at school and in the community and the natural surroundings. Research method In general, the research method is defined as a scientific activity that is planned, structured, systematic, and has specific goals, both practical and theoretical. It is said to be a scientific activity because it is research with scientific and theoretical aspects. planned because research must be planned with due regard to time, funds and accessibility to places and data. The data source is the subject from which the research data was obtained. Based on the source, the data is divided into primary data which is the source of data obtained by the researcher from respondents through interviews with interviewees. Secondary data is data obtained by the researcher indirectly providing data to data collectors, for example through other people or documents. The research results show that students choose to deepen their knowledge and hone their skills by continuing their education to a higher level, in this case tertiary institutions. Thus they will be able to continue to be able to compete with the knowledge and skills they acquire when they have completed their studies from tertiary institutions. The factors that influence students' interest in continuing their studies to tertiary institutions are divided into 2, namely influencing factors and inhibiting factors as follows: influencing students' interest in continuing their studies to tertiary institutions (a) Internal factors include willingness, academic success (b) External factors include: Parents' socioeconomic status, Environment (family environment, community environment, school environment, school environment).